First Trial Of The HIV1 Vaccine In Africa: Ugandan Experience - Mugerwa, Roy D.; Kaleebu, Pontiano; Mugyenyi, Peter; Mbidde, Edward Katongole; Hom, David L.; Byaruhanga, Rose; Salata, Robert A.; Ellner, Jerrold J.; HIV1 Vaccine Trial Group (Bmj, 2002)
Trials of the HIV1 vaccine have been conducted in Europe, North America, Brazil, China, and Thailand.1 The first trial of a candidate vaccine in Africa was recently completed in Uganda. It involved a randomised, placebo controlled trial of a vaccine in healthy volunteers at low risk of HIV infection.2 3 The vaccine, called “ALVACHIV,” uses a live recombinant canarypox vector to express envelope and core genes of HIV1. Many commentators predicted that it would be difficult to conduct trials of HIV vaccines in developing countries because of scientific, sociobehavioural, ethical, and logistical barriers.4–8 Before we started the trial in Uganda, we gathered data to help us overcome these potential barriers. We collected epidemiological9 and sociobehavioural10 data about people who had participated in studies that looked at preparing for trials of the HIV vaccine. These data showed the prevalence and incidence of HIV, behaviours placing people at risk of becoming infected with HIV, and the social acceptability of a vaccine against HIV.9–11 The people received detailed education and counselling about infection with HIV and about HIV vaccines, and we recruited some for our trial.11We organised three open workshops at the HIV candidate vaccine trial workshop in Kampala in 1996 to gain consensus from scientists, policy makers, community representatives, and the media about how to undertake research into HIV vaccines. Despite these initiatives to solve problems before the trial began, we still encountered many barriers. In this article, we discuss these barriers and the strategiesthat we developed to overcome them.